(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article explores the effectiveness of blended learning models in foreign language education by integrating traditional teaching methods with digital technologies. The study analyzes how blended learning can enhance students’ language proficiency and engagement. It also examines the challenges faced by educators and provides recommendations for the effective application of this approach. The findings reveal that blended learning models address diverse student needs and improve educational quality.